2016
DOI: 10.1177/0014402916671517
|View full text |Cite
|
Sign up to set email alerts
|

Literacy Learning Cohorts

Abstract: Two professional development (PD) models for teachers were compared on teacher and student outcomes. Special education teachers participated in Literacy Learning Cohorts (LLC), a PD innovation designed to improve content and pedagogical knowledge for providing reading instruction to upper elementary students with learning disabilities. The LLC, based on Desimone’s (2009) framework, included 2 days of initial PD with follow-up meetings, coaching, and video self-analysis. A comparison group received only 2 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 56 publications
(103 reference statements)
4
42
0
Order By: Relevance
“…A closer examination of acceptable and high quality studies (n = 9) showed the same trend, with 21 large (g = 0.93-55.32), three moderate (g = 0.51-0.76), and six small (g = 0.19-0.36) effect sizes found. Further, although anal ysis revealed a few statistically nonsignificant differences, issues with measurement and training in these studies were raised (Brownell et al, 2017;Goldfeld et al, 2021;Purvis et al, 2016). Specifically, Purvis et al (2016) used a syllable counting task, likely easy for participants before any training, and Brownell et al (2017) had weak reliabil ity of their phonics knowledge measure (i.e., α = .50) and sample size limitations.…”
Section: Phonicsmentioning
confidence: 86%
See 1 more Smart Citation
“…A closer examination of acceptable and high quality studies (n = 9) showed the same trend, with 21 large (g = 0.93-55.32), three moderate (g = 0.51-0.76), and six small (g = 0.19-0.36) effect sizes found. Further, although anal ysis revealed a few statistically nonsignificant differences, issues with measurement and training in these studies were raised (Brownell et al, 2017;Goldfeld et al, 2021;Purvis et al, 2016). Specifically, Purvis et al (2016) used a syllable counting task, likely easy for participants before any training, and Brownell et al (2017) had weak reliabil ity of their phonics knowledge measure (i.e., α = .50) and sample size limitations.…”
Section: Phonicsmentioning
confidence: 86%
“…Thirteen studies addressed phonics knowledge (Brady et al, 2009;Brownell et al, 2017;Carreker et al, 2010;Englert et al, 2020;Goldfeld et al, 2021;Gormley & Ruhl, 2007;Leader Janssen & Rankin Erickson, 2013;McMahan et al, 2019;Peltier et al, 2020;Purvis et al, 2016;Spear Swerling, 2009;Spear Swerling & Brucker, 2003, 2004. Across these studies (see Table 3), PST coursework focused on building orthographic knowledge and the systematic, explicit teach ing of word decoding to young students.…”
Section: Phonicsmentioning
confidence: 99%
“…Two existing studies show that such PD structures might be useful in improving instruction for students with disabilities and struggling readers (Gersten et al, 2010; Mutch-Jones et al, 2012), however, neither evaluated the effectiveness of content-focused LS for promoting coordinated instruction across tiers of RTI. Randomized controlled trials of such approaches to LS are important for determining whether the collaborative PD structure employed in our study is an evidence-based approach for improving teachers’ skill in providing coordinated RTI instruction, and for determining if a content-focused LS approach is more effective than other collaborative approaches, such as LS without content-focused PD workshops (Saito & Atencio, 2013), content-focused PD followed by coaching (Brownell et al, 2017), and professional learning communities (Vescio et al, 2008). Identifying which collaborative PD structure is most effective and efficient at promoting coordination of evidence-based practices across tiers would be useful for school leaders in their efforts to create and maintain effective RTI systems.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative research aims to understand the world from the participant's point of view (Corbin & Strauss, 2015). Consequently, some studies emphasize the needs of special education teachers (Brownell et al, 2017) and explore their experiences from their perspectives. The ethical approval of this study was granted by the Ministry of Education (reference no.…”
Section: Methodsmentioning
confidence: 99%